Oligopoly structure in the cryptocurrency market - Nenad Tomić (Anali Ekonomskog fakulteta u Subotici, 2024)
Blockchain technology has been announced as the driving force behind the democratization of digital business. Various interest groups believed that cryptocurrencies would enable fast, cheap and anonymous payments over the Internet. The absence of a central institution and the possibility of the participation of the wider community in the maintenance of the system should have created electronic money adapted to individuals, not the financial elite. However, the question arises whether cryptocurrencies really provide equal opportunities for all participants. The subject of the paper is the degree of centralization of the most famous cryptocurrency systems in terms of wealth distribution and the possibility of participation in their maintenance. The goal of the paper is to determine the degree of inequality in various aspects of the functioning of the cryptocurrency system. The results of the analysis indicate that cryptocurrencies function separately from the traditional financial system, but do not enable the financial inclusion of marginalized social groups. No current cryptocurrency community provides equality of participants, neither in terms of mining, nor in terms of wealth distribution. It can be concluded that the mining of cryptocurrencies and their secondary circulation show clear characteristics of oligopolistic structures.